Distance learning of a foreign language in the context of neuropedagogical factors - Lakhmotova, Yuliia; Sadovets, Olesia; Orlovska, Olha; Martynyuk, Olena; Myroshnychenko, Viktoriia; Lebedieva, Liudmyla (LUMEN Publishing, 2024)
The relevance of the article lies in the fact that in our time, the organization of distance learning when learning a foreign language is extremely relevant. The purpose of the article: to find out the main terms and forms of distance learning; consider the features of online education; explore platforms for the convenient organization of online learning; highlight the advantages and disadvantages of distance learning when learning a foreign language as an aspect of neuropedagogical training. Work methods: compare the analysis of literary sources on the research problem; to systematize the researched; compare the benefits of distance learning. The novelty of using mobile technologies, which is extremely effective and necessary when learning a foreign language online. Results: synchronous, asynchronous and mixed learning are distinguished among distance learning forms. E-learning is a basic form that has both advantages and disadvantages. Blackboard is widely used among e-learning platforms. Conclusion: the role of the teacher who uses interactive forms of learning for mobile learning has changed. The Internet provides a wide selection of modern materials for learning a foreign language. Students and teachers accept online education with desire and interest, increase their information and communication competence. Physical activity is necessary for long-term work on educational platforms.
Keywords: online; synchronous; asynchronous; distance education; virtual class; mobile learning; neuropedagogy